2007
DOI: 10.1117/12.752679
|View full text |Cite
|
Sign up to set email alerts
|

Persistent photoconductivity of InP nanowire photoconductors bridged between amorphous silicon electrodes

Abstract: We fabricated a photo-conducting device with InP nanowires bridged between phosphorous-doped hydrogenated amorphous silicon electrodes. Photoresponse of the device with DC bias was characterized with a white light source and a 630nm He-Ne laser. Experimental results from a large number of devices demonstrate a persistent photoconductivity, a very unique feature of interest. After the light source is shut off, the photogenerated excess carriers recombine very slowly over time and the effect is manifested in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Both bulk defects, such as vacancies, impurities, and surface states can collectively contribute to the long trapping of photogenerated excess carriers and manifest as a temporary boost in dark conductivity, which may exist for days or even years [316]. PPC studies have been reported for some structures, e.g., GaN thin films [311], [313], [314], [317]- [320], InGaN epitaxial films [315], GaNNWs [321], and InP NWs [322].…”
Section: Surface Traps Passivation and Persistent Photoconductivitymentioning
confidence: 99%
“…Both bulk defects, such as vacancies, impurities, and surface states can collectively contribute to the long trapping of photogenerated excess carriers and manifest as a temporary boost in dark conductivity, which may exist for days or even years [316]. PPC studies have been reported for some structures, e.g., GaN thin films [311], [313], [314], [317]- [320], InGaN epitaxial films [315], GaNNWs [321], and InP NWs [322].…”
Section: Surface Traps Passivation and Persistent Photoconductivitymentioning
confidence: 99%